2004
DOI: 10.1007/s10397-003-0001-0
|View full text |Cite
|
Sign up to set email alerts
|

Endosalpingiosis, an unrecognized condition: report and literature review

Abstract: This study involves an audit of cases of endosalpingiosis diagnosed at a major teaching hospital and a review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 18 publications
0
40
0
Order By: Relevance
“…Hesseling et al (5) showed no link between the two. There are also links in the literature between endosalpingiosis and serous borderline ovarian tumours (5) inflammatory tubal disease (9), and endometriosis (1,4,5). No study has yet directly compared endosalpingiosis and endometriosis to see if there are differences in their clinical presentations and demographics.…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…Hesseling et al (5) showed no link between the two. There are also links in the literature between endosalpingiosis and serous borderline ovarian tumours (5) inflammatory tubal disease (9), and endometriosis (1,4,5). No study has yet directly compared endosalpingiosis and endometriosis to see if there are differences in their clinical presentations and demographics.…”
mentioning
confidence: 94%
“…There have been tentative links made between endosalpingiosis and chronic pelvic pain (3)(4)(5)(6)(7)(8) whereas other studies report it as an asymptomatic condition (1,5).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…It is derived from the mullerian system and is seen in the pelvic and lower abdominal peritoneum. Colon, bladder, appendix, paraaortic and pelvic lymph nodes are the sites specified in the case reports (2)(3)(4). Patients are almost always asymptomatic and it very rarely presents as a large cystic mass known as florid cystic endosalpingiosis (5).…”
Section: Introductionmentioning
confidence: 99%